Current collector for a negative electrode-free battery, method for manufacturing the same, and sodium-ion battery
Patent Information
- Application Number
- CN202611162315.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-16
AI Technical Summary
针对现有技术存在的不足,本发明的目的在于提供一种无负极电池用集流体及其制备方法与应用,以解决现有集流体因死钠积累、缓冲功能衰减而导致的库仑效率低和循环寿命短的问题
[0039] This invention prepares a NiTi foam matrix through a layered gradient pore-forming and pressure sintering process, followed by chemical copper plating to obtain a composite current collector. A longitudinal gradient pore structure is incorporated along the thickness direction. Under low-temperature martensitic soft conditions, the current collector pores expand, reserving sufficient space to accommodate sodium deposition. During discharge, the Joule heating of the battery causes NiTi to transform into an austenitic contractile phase. The entire matrix applies uniform pressure to the sodium deposition layer, with stress concentration in the lower small-pore region leading to preferential contraction, driving dense sodium deposition at the bottom of the current collector and inhibiting top-down dendrite growth. The upper large-pore region simultaneously buffers volume expansion stress. After discharge, the battery cools naturally, and the NiTi matrix returns to its expanded soft state, reforming large-size sodium storage pores. This invention relies solely on the battery's own heat generation and dissipation to achieve adaptive pore regulation, upgrading the traditional passive sodium storage mode of the current collector to active stress-regulated sodium storage. The integrated function of the matrix and gradient pores avoids coating failure issues, effectively reduces dead sodium generation, and improves the battery's long-cycle stability.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology, and relates to a current collector for a negative electrode-free battery and its preparation method, as well as a sodium-ion battery. Background Technology
[0002] In recent years, with the rise in lithium resource prices and the rapid growth in global energy storage demand, sodium-ion batteries, based on abundant, widely distributed, and low-cost sodium, have attracted widespread attention and are considered an important supplement to lithium-ion batteries in the fields of energy storage and power. Hard carbon, due to its large interlayer spacing, disordered structure, and abundant sodium storage sites, is currently the most promising anode material for sodium-ion batteries. Precursors for hard carbon are widely available, including biomass, coal, resin, and asphalt. Among these, biomass, with its natural hierarchical porous structure, renewability, and low cost, is considered an ideal raw material for preparing high-performance hard carbon. However, traditional sodium-ion batteries using hard carbon and other anode active materials have limited sodium storage capacity, making it difficult to meet the needs of high-energy storage systems. Electroplated anode sodium-ion batteries, by discarding the pre-placed active material on the anode side, use only the current collector (such as copper or aluminum foil) as the nominal anode during battery assembly. During the first charge, sodium ions are extracted from the cathode material and electrochemically deposited directly on the current collector surface to form a sodium metal anode, thereby maximizing energy density.
[0003] During the charging and discharging process of sodium-plated negative electrodes, repeated deposition / stripping of sodium metal causes drastic volume changes, leading to interfacial instability. Therefore, three-dimensional porous structures have become a mainstream buffering method. For example, CN121862753A provides physical buffering space through a three-dimensional conductive network framework; CN119447319A buffers volume changes through a three-dimensional honeycomb bismuth nanosheet structure.
[0004] However, the aforementioned solutions are essentially "passive buffers," meaning the pores are merely pre-set physical containers where sodium deposits and passively accommodates volume expansion. As the reserved spaces are gradually filled with each cycle, the buffering function is lost, and subsequent volume expansion stress directly acts on the framework, leading to structural fatigue or even collapse. Furthermore, passive buffering cannot handle existing dead sodium; instead, the high specific surface area exacerbates side reactions and irreversibly consumes active sodium. Therefore, existing solutions lack active control capabilities, cannot actively contract or expand to create space based on charging and discharging phases, and cannot actively reactivate dead sodium. Summary of the Invention
[0005] Existing electroplated negative electrode current collectors struggle to simultaneously achieve high sodium storage capacity, long cycle stability, and effective dendrite growth suppression. To address these shortcomings, this invention aims to provide a current collector for negative electrode-free batteries, its preparation method, and its applications, thereby resolving the problems of low coulombic efficiency and short cycle life caused by dead sodium accumulation and buffer function degradation in existing current collectors.
[0006] To achieve this objective, the present invention adopts the following technical solution:
[0007] In a first aspect, the present invention provides a method for preparing a current collector for a negative electrodeless battery, the method comprising:
[0008] S1. The mixed powder is laid in layers and then pre-pressed to obtain a green body;
[0009] The mixed powder includes NiTi alloy powder, pore-forming agent and dispersant; along the thickness direction of the layer, the average particle size of the pore-forming agent increases gradually in different layers of the mixed powder.
[0010] S2. In a protective atmosphere, the green compact is subjected to pressure sintering; then, under pressure holding conditions, it is cooled to room temperature, the pressure is removed, and the sintered product is obtained.
[0011] S3. Wash the sintered product with water to remove the pore-forming agent, then acid wash to remove the surface oxide layer, and dry to obtain NiTi foam;
[0012] S4. The NiTi foam is immersed in a chemical copper plating solution for chemical copper plating, and after washing and drying, the current collector for the negative electrodeless battery is obtained.
[0013] This invention prepares a NiTi foam matrix through a layered gradient pore-forming and pressure sintering process, followed by chemical copper plating to obtain a composite current collector. A longitudinal gradient pore structure is incorporated along the thickness direction. Under low-temperature martensitic soft conditions, the current collector pores expand, reserving sufficient space to accommodate sodium deposition. During discharge, the Joule heating of the battery causes NiTi to transform into an austenitic contractile phase. The entire matrix applies uniform pressure to the sodium deposition layer, with stress concentration in the lower small-pore region leading to preferential contraction, driving dense sodium deposition at the bottom of the current collector and inhibiting top-down dendrite growth. The upper large-pore region simultaneously buffers volume expansion stress. After discharge, the battery cools naturally, and the NiTi matrix returns to its expanded soft state, reforming large-size sodium storage pores. This invention relies solely on the battery's own heat generation and dissipation to achieve adaptive pore regulation, upgrading the traditional passive sodium storage mode of the current collector to active stress-regulated sodium storage. The integrated function of the matrix and gradient pores avoids coating failure issues, effectively reduces dead sodium generation, and improves the battery's long-cycle stability.
[0014] In some embodiments, the average particle size of the NiTi alloy powder is 20 μm to 30 μm.
[0015] In some embodiments, the method for preparing the NiTi alloy powder includes: mixing Ni powder and Ti powder, performing arc melting in a protective atmosphere, cooling and casting to obtain NiTi alloy rods; and crushing the NiTi alloy rods to obtain NiTi alloy powder.
[0016] In some embodiments, the temperature of the electric arc melting is 1600°C to 1700°C.
[0017] In some embodiments, the arc melting time is 10 min to 20 min.
[0018] In some embodiments, the cooling rate of the cooling casting is 10°C / min to 20°C / min.
[0019] In some embodiments, the layered application of the mixed powder includes sequentially applying a lower layer of mixed powder, a middle layer of mixed powder, and an upper layer of mixed powder;
[0020] In the lower layer of mixed powder, the average particle size of the pore-forming agent is 50μm~125μm;
[0021] In the intermediate layer mixed powder, the average particle size of the pore-forming agent is 125μm~250μm;
[0022] In the upper mixed powder, the average particle size of the pore-forming agent is 250μm~500μm.
[0023] In some embodiments, the volume ratio of NiTi alloy powder to pore-forming agent in the mixed powder is (50~70):(50~30).
[0024] In some embodiments, the pre-compression molding pressure is 50MPa~100MPa.
[0025] In some embodiments, the heating rate of the pressure sintering is 2°C / min to 10°C / min.
[0026] In some embodiments, the sintering temperature of the pressure sintering is 900°C to 1000°C.
[0027] In some embodiments, the pressure of the pressure sintering is 20 MPa to 30 MPa.
[0028] In some embodiments, the holding time for the pressure sintering is 3h to 6h.
[0029] In some embodiments, the cooling rate is 10°C / min to 20°C / min.
[0030] In some embodiments, the water washing method includes ultrasonic cleaning.
[0031] In some embodiments, the temperature of the water wash is 50°C to 80°C.
[0032] In some embodiments, the washing time is 4 to 8 hours.
[0033] In some embodiments, the pickling is performed using a hydrofluoric acid solution with a concentration of 3wt% to 8wt%.
[0034] In some embodiments, the pickling time is 20s to 60s.
[0035] Secondly, the present invention provides a current collector for a negative electrode-free battery, wherein the current collector for a negative electrode-free battery is prepared by the preparation method described in the first aspect.
[0036] Thirdly, the present invention provides a sodium-ion battery, the sodium-ion battery comprising a current collector for a negative electrode-free battery prepared by the preparation method described in the first aspect, or comprising a current collector for a negative electrode-free battery as described in the second aspect.
[0037] The numerical range described in this invention includes not only the point values listed above, but also any point values within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values included in the range.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] This invention prepares a NiTi foam matrix through a layered gradient pore-forming and pressure sintering process, followed by chemical copper plating to obtain a composite current collector. A longitudinal gradient pore structure is incorporated along the thickness direction. Under low-temperature martensitic soft conditions, the current collector pores expand, reserving sufficient space to accommodate sodium deposition. During discharge, the Joule heating of the battery causes NiTi to transform into an austenitic contractile phase. The entire matrix applies uniform pressure to the sodium deposition layer, with stress concentration in the lower small-pore region leading to preferential contraction, driving dense sodium deposition at the bottom of the current collector and inhibiting top-down dendrite growth. The upper large-pore region simultaneously buffers volume expansion stress. After discharge, the battery cools naturally, and the NiTi matrix returns to its expanded soft state, reforming large-size sodium storage pores. This invention relies solely on the battery's own heat generation and dissipation to achieve adaptive pore regulation, upgrading the traditional passive sodium storage mode of the current collector to active stress-regulated sodium storage. The integrated function of the matrix and gradient pores avoids coating failure issues, effectively reduces dead sodium generation, and improves the battery's long-cycle stability. Detailed Implementation
[0040] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0041] The "range" disclosed in this invention can be defined in the form of a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of the specific range. This type of range definition can include or exclude endpoints; any endpoint can be independently included or excluded, and they can be arbitrarily combined, meaning any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60~120 and 80~110 are listed for specific parameters, it is understood that ranges of 60~110 and 80~120 are also expected. Furthermore, if minimum range values 1 and 2 are listed, and maximum range values 3, 4, and 5 are also listed, then the following ranges are all expected: 1~3, 1~4, 1~5, 2~3, 2~4, and 2~5. In this invention, unless otherwise stated, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0" and "5" have been listed in this article; "0~5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is described as an integer ≥2, it is equivalent to listing integers such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For instance, when a parameter is described as an integer selected from "2~10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9, and 10.
[0042] In this invention, "a combination of at least two" refers to a quantity greater than or equal to two, unless otherwise specified. For example, "any combination of one or at least two" means one or more or more items. It can be understood that when referring to "a combination of at least two," it refers to any suitable combination of multiple items, that is, a combination of "at least two" items carried out in a manner that does not conflict with and enables the implementation of this invention.
[0043] Unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions.
[0044] The term "embodiment" as used in this invention means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment or implementation of the invention. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a mutually exclusive, independent, or alternative embodiment. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described in this invention can be combined with other embodiments.
[0045] Those skilled in the art will understand that the order in which the steps are written in the methods of the various embodiments does not imply a strict execution order. The detailed execution order of each step should be determined by its function and possible internal logic. Unless otherwise specified, all steps of the present invention may be performed sequentially or randomly, but are preferably performed sequentially. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), meaning that step (c) can be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0046] In this invention, open-ended technical features or solutions described using terms such as "comprising" do not exclude additional members beyond those listed unless otherwise specified. They can be considered as providing both closed-ended features or solutions comprised of the listed members and open-ended features or solutions that include additional members beyond the listed members. For example, A includes a1, a2, and a3. Unless otherwise specified, it may also include other members or exclude additional members. This can be considered as providing both technical features or solutions where "A is composed of a1, a2, and a3" or "A is selected from a1, a2, and a3," and technical features or solutions where "A includes not only a1, a2, and a3, but also other members."
[0047] In this invention, unless otherwise specified, the features or solutions corresponding to "and / or" include any one of two or more of the related listed items, as well as any and all combinations of the related listed items. These arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. For example, "A and / or B" represents a group consisting of A, B, and "a combination of A and B". "Containing A and / or B" can mean "containing A, containing B, and containing A and B", or "containing A, containing B, or containing A and B", and can be appropriately understood according to the context.
[0048] In this invention, the terms "first aspect," "second aspect," "third aspect," "fourth aspect," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first," "second," "third," "fourth," etc., serve only as a non-exhaustive enumeration and should be understood not to constitute a closed limitation on the quantity.
[0049] In this invention, "optional" means that something is optional, that is, it refers to either "with" or "without". If there are multiple "optional" options in a technical solution, unless otherwise specified, and there are no contradictions or mutual constraints, then each "optional" option is independent.
[0050] In this invention, "room temperature" generally refers to 4℃~35℃, and can refer to 20℃±5℃. In some embodiments of this invention, room temperature refers to 20℃~30℃.
[0051] In a first aspect, the present invention provides a method for preparing a current collector for a negative electrodeless battery, the method comprising:
[0052] S1. The mixed powder is laid in layers and then pre-pressed to obtain a green body;
[0053] The mixed powder includes NiTi alloy powder, pore-forming agent and dispersant; along the thickness direction of the layer, the average particle size of the pore-forming agent increases gradually in different layers of the mixed powder.
[0054] S2. In a protective atmosphere, the green compact is subjected to pressure sintering; then, under pressure holding conditions, it is cooled to room temperature, the pressure is removed, and the sintered product is obtained.
[0055] S3. Wash the sintered product with water to remove the pore-forming agent, then acid wash to remove the surface oxide layer, and dry to obtain NiTi foam;
[0056] S4. The NiTi foam is immersed in a chemical copper plating solution for chemical copper plating, and after washing and drying, the current collector for the negative electrodeless battery is obtained.
[0057] This invention prepares a NiTi foam matrix through a layered gradient pore-forming and pressure sintering process, followed by chemical copper plating to obtain a composite current collector. A longitudinal gradient pore structure is incorporated along the thickness direction. Under low-temperature martensitic soft conditions, the current collector pores expand, reserving sufficient space to accommodate sodium deposition. During discharge, the Joule heating of the battery causes NiTi to transform into an austenitic contractile phase. The entire matrix applies uniform pressure to the sodium deposition layer, with stress concentration in the lower small-pore region leading to preferential contraction, driving dense sodium deposition at the bottom of the current collector and inhibiting top-down dendrite growth. The upper large-pore region simultaneously buffers volume expansion stress. After discharge, the battery cools naturally, and the NiTi matrix returns to its expanded soft state, reforming large-size sodium storage pores. This invention relies solely on the battery's own heat generation and dissipation to achieve adaptive pore regulation, upgrading the traditional passive sodium storage mode of the current collector to active stress-regulated sodium storage. The integrated function of the matrix and gradient pores avoids coating failure issues, effectively reduces dead sodium generation, and improves the battery's long-cycle stability.
[0058] In some embodiments, the average particle size of the NiTi alloy powder is 20μm to 30μm, for example, it can be 20μm, 21μm, 24μm, 25μm, 27μm, 28μm or 30μm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0059] In some embodiments, the method for preparing the NiTi alloy powder includes: mixing Ni powder and Ti powder, performing arc melting in a protective atmosphere, cooling and casting to obtain NiTi alloy rods; and crushing the NiTi alloy rods to obtain NiTi alloy powder.
[0060] Optionally, the molar ratio of Ni to Ti in the Ni powder and Ti powder is 1:1. By setting appropriate arc melting temperature and cooling rate of cooling casting, a uniform austenitic matrix can be obtained, making the phase transformation temperature As (austenite initiation temperature) of NiTi alloy powder approximately 35℃ and Af (austenite transformation completion temperature) approximately 55℃, matching the battery discharge temperature rise to trigger skeleton shrinkage.
[0061] In some embodiments, the temperature of the electric arc melting is 1600°C to 1700°C, for example, 1600°C, 1620°C, 1640°C, 1650°C, 1660°C, 1680°C or 1700°C, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0062] In some embodiments, the arc melting time is 10 min to 20 min, for example, it can be 10 min, 12 min, 15 min, 16 min, 18 min or 20 min, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0063] In some embodiments, the cooling rate of the cooling casting is 10°C / min to 20°C / min, for example, it can be 10°C / min, 12°C / min, 15°C / min, 16°C / min, 18°C / min or 20°C / min, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0064] In some embodiments, the layered application of the mixed powder includes sequentially applying a lower layer of mixed powder, a middle layer of mixed powder, and an upper layer of mixed powder;
[0065] In the lower layer of mixed powder, the average particle size of the pore-forming agent is 50μm~125μm, for example, it can be 50μm, 60μm, 80μm, 100μm, 120μm or 125μm, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0066] In the intermediate layer mixed powder, the average particle size of the pore-forming agent is 125μm~250μm, for example, it can be 125μm, 150μm, 180μm, 200μm, 210μm, 240μm or 250μm, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0067] In the upper mixed powder, the average particle size of the pore-forming agent is 250μm to 500μm, for example, it can be 250μm, 280μm, 300μm, 320μm, 350μm, 380μm, 400μm, 420μm, 450μm, 480μm or 500μm, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0068] Optionally, the thickness of the lower layer of mixed powder is 100μm to 180μm, for example, it can be 100μm, 120μm, 150μm, 160μm or 180μm, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0069] Optionally, the thickness of the intermediate mixed powder layer is 220μm to 350μm, for example, it can be 220μm, 240μm, 250μm, 280μm, 300μm, 320μm or 350μm, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0070] Optionally, the thickness of the upper mixed powder layer is 350μm to 550μm, for example, it can be 350μm, 400μm, 420μm, 450μm, 480μm, 500μm, 540μm or 550μm, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0071] This invention uses pore-forming agents with different average particle sizes in mixed powders of different layers, so that the pores in the lower layer can preferentially heat up and trigger shrinkage, inducing dense deposition at the bottom.
[0072] In some embodiments, the volume ratio of NiTi alloy powder to pore-forming agent in the mixed powder is (50~70):(50~30), for example, it can be 50:50, 60:40 or 70:30, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0073] Optionally, the dispersant in this invention includes anhydrous ethanol. The role of the dispersant is to uniformly mix the NiTi alloy powder and the pore-forming agent. This invention does not specify a particular amount, as long as the dispersant can perform its function.
[0074] Appropriate pre-compression forming pressure can ensure the strength of the green body without damaging the gradation, and achieve controllable thermal response sequence.
[0075] In some embodiments, the pre-compression pressure is 50MPa to 100MPa, for example, it can be 50MPa, 60MPa, 70MPa, 80MPa, 90MPa or 100MPa, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0076] Appropriate pressure during sintering makes the pore walls suitable for transmitting phase transformation stress, and the combination of heating rate and holding time can make the martensite variants have consistent orientation and stabilize As / Af at the target value.
[0077] In some embodiments, the heating rate of the pressure sintering is 2°C / min to 10°C / min, for example, it can be 2°C / min, 4°C / min, 5°C / min, 6°C / min, 8°C / min or 10°C / min, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0078] In some embodiments, the sintering temperature of the pressure sintering is 900℃~1000℃, for example, it can be 900℃, 920℃, 940℃, 950℃, 960℃, 980℃ or 1000℃, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0079] In some embodiments, the pressure of the pressure sintering is 20MPa to 30MPa, for example, it can be 20MPa, 21MPa, 24MPa, 25MPa, 27MPa, 28MPa or 30MPa, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0080] In some embodiments, the holding time for pressure sintering is 3h to 6h, for example, it can be 3h, 4h, 5h or 6h, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0081] In some embodiments, the cooling rate is 10°C / min to 20°C / min, for example, it can be 10°C / min, 12°C / min, 15°C / min, 16°C / min, 18°C / min or 20°C / min, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0082] Suitable water washing conditions can completely remove pore-forming agents; suitable acid washing conditions can prevent excessive corrosion that could lead to phase transition temperature drift.
[0083] In some embodiments, the water washing method includes ultrasonic cleaning.
[0084] In some embodiments, the water washing temperature is 50°C to 80°C, for example, it can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0085] In some embodiments, the washing time is 4h to 8h, for example, it can be 4h, 5h, 6h, 7h or 8h, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0086] In some embodiments, the pickling is performed using a hydrofluoric acid solution with a concentration of 3wt% to 8wt%, for example, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, or 8wt%, but not limited to the listed values; other unlisted values within the range are also applicable.
[0087] In some embodiments, the pickling time is 20s to 60s, for example, it can be 20s, 30s, 40s, 50s or 60s, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0088] Optionally, the electroless copper plating solution can be composed of equal volumes of solution A and solution B. Solution A consists of: 10 g / L~15 g / L NaOH, 10 g / L~15 g / L CuSO4·5H2O, and 25 g / L~32 g / L NaKC4H4O6·4H2O, with water as the solvent; solution B is a 9 mL / L~10 mL / L methanol aqueous solution.
[0089] Optionally, the electroless copper plating time is 1h to 3h, for example, it can be 1h, 2h or 3h, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0090] As a preferred embodiment of the preparation method provided in the first aspect of the present invention, the preparation method includes:
[0091] (1) Mix Ni powder and Ti powder, perform electric arc melting in an argon atmosphere, and cool and cast to obtain NiTi alloy rods; crush the NiTi alloy rods to obtain NiTi alloy powder with an average particle size of 20μm~30μm;
[0092] The electric arc melting temperature is 1600℃~1700℃, and the time is 10min~20min;
[0093] The cooling rate of the cooling casting is 10℃ / min~20℃ / min;
[0094] (2) The mixed powder is laid in layers and then pre-pressed with a pressure of 50MPa~100MPa to obtain a green body;
[0095] The mixed powder comprises NiTi alloy powder, pore-forming agent and dispersant; in the mixed powder, the volume ratio of NiTi alloy powder to pore-forming agent is (50~70):(50~30);
[0096] The layered mixed powder comprises sequentially laying a lower layer of mixed powder with a thickness of 100μm~180μm, a middle layer of mixed powder with a thickness of 220μm~350μm, and an upper layer of mixed powder with a thickness of 350μm~550μm; in the lower layer of mixed powder, the average particle size of the pore-forming agent is 50μm~125μm; in the middle layer of mixed powder, the average particle size of the pore-forming agent is 125μm~250μm; and in the upper layer of mixed powder, the average particle size of the pore-forming agent is 250μm~500μm.
[0097] (3) In an argon atmosphere, the green blank is subjected to pressure sintering; then, under pressure holding conditions, it is cooled to room temperature at a cooling rate of 10℃ / min~20℃ / min, the pressure is removed, and the sintered product is obtained.
[0098] The heating rate of the pressure sintering is 2℃ / min~10℃ / min, the sintering temperature is 900℃~1000℃, the pressure is 20MPa~30MPa, and the holding time is 3h~6h.
[0099] (4) The sintered product is washed with water to remove the pore-forming agent, then acid-washed to remove the surface oxide layer, and dried to obtain NiTi foam;
[0100] The water washing method includes ultrasonic cleaning at a temperature of 50℃~80℃ for 4h~8h.
[0101] The pickling is carried out using a hydrofluoric acid solution with a concentration of 3wt%~8wt% for 20s~60s;
[0102] (5) The NiTi foam is immersed in a chemical copper plating solution for 1h~3h for chemical copper plating, and then washed and dried to obtain the current collector for the negative electrodeless battery;
[0103] The electroless copper plating solution can be composed of equal volumes of solution A and solution B; solution A consists of 10 g / L to 15 g / L NaOH, 10 g / L to 15 g / L CuSO4·5H2O, and 25 g / L to 32 g / L NaKC4H4O6·4H2O, with water as the solvent; solution B is a methanol aqueous solution with a concentration of 9 mL / L to 10 mL / L.
[0104] Secondly, the present invention provides a current collector for a negative electrode-free battery, wherein the current collector for a negative electrode-free battery is prepared by the preparation method described in the first aspect.
[0105] Thirdly, the present invention provides a sodium-ion battery, the sodium-ion battery comprising a current collector for a negative electrode-free battery prepared by the preparation method described in the first aspect, or comprising a current collector for a negative electrode-free battery as described in the second aspect.
[0106] Example 1
[0107] This embodiment provides a method for preparing a current collector for a negative electrodeless battery, including:
[0108] (1) Ni powder and Ti powder are mixed in a molar ratio of 1:1, and then arc-melted in an argon atmosphere. The mixture is then cooled and cast to obtain NiTi alloy rods. The NiTi alloy rods are crushed to obtain NiTi alloy powder with an average particle size of 25 μm.
[0109] The electric arc melting temperature is 1650℃ and the time is 15 minutes;
[0110] The cooling rate of the cooling casting is 15℃ / min;
[0111] (2) The mixed powder is laid in layers and then pre-pressed with a pressure of 80MPa to obtain a green body;
[0112] The mixed powder comprises NiTi alloy powder, pore-forming agent (ammonium bicarbonate) and dispersant (anhydrous ethanol); the volume ratio of NiTi alloy powder to pore-forming agent in the mixed powder is 60:40.
[0113] The layered mixed powder comprises sequentially laying a lower layer of mixed powder with a thickness of 150 μm, a middle layer of mixed powder with a thickness of 300 μm, and an upper layer of mixed powder with a thickness of 450 μm; in the lower layer of mixed powder, the average particle size of the pore-forming agent is 80 μm; in the middle layer of mixed powder, the average particle size of the pore-forming agent is 200 μm; and in the upper layer of mixed powder, the average particle size of the pore-forming agent is 350 μm.
[0114] (3) In an argon atmosphere, the green blank is subjected to pressure sintering; then, under pressure holding conditions, it is cooled to room temperature at a cooling rate of 15℃ / min, the pressure is removed, and the sintered product is obtained.
[0115] The heating rate of the pressure sintering is 6℃ / min, the sintering temperature is 950℃, the pressure is 25MPa, and the holding time is 4h.
[0116] (4) The sintered product is washed with water to remove the pore-forming agent, then acid-washed to remove the surface oxide layer, and dried to obtain NiTi foam;
[0117] The water washing method includes ultrasonic cleaning at a temperature of 65°C for 6 hours;
[0118] The pickling was carried out using a 5 wt% hydrofluoric acid solution for 40 seconds.
[0119] (5) The NiTi foam is immersed in a chemical copper plating solution for 2 hours for chemical copper plating, and then washed and dried to obtain the current collector for the negative electrodeless battery;
[0120] The electroless copper plating solution can be composed of equal volumes of solution A and solution B; solution A consists of 12 g / L NaOH, 13 g / L CuSO4·5H2O, and 29 g / L NaKC4H4O6·4H2O, with water as the solvent; solution B is a 9.5 mL / L methanol aqueous solution.
[0121] Example 2
[0122] This embodiment provides a method for preparing a current collector for a negative electrodeless battery, including:
[0123] (1) Ni powder and Ti powder are mixed in a molar ratio of 1:1, and then arc-melted in an argon atmosphere. The mixture is then cooled and cast to obtain NiTi alloy rods. The NiTi alloy rods are crushed to obtain NiTi alloy powder with an average particle size of 20 μm.
[0124] The electric arc melting temperature is 1600℃ and the time is 20 minutes;
[0125] The cooling rate of the cooling casting is 10℃ / min;
[0126] (2) The mixed powder is laid in layers and then pre-pressed with a pressure of 50MPa to obtain a green body;
[0127] The mixed powder comprises NiTi alloy powder, pore-forming agent (ammonium bicarbonate) and dispersant (anhydrous ethanol); the volume ratio of NiTi alloy powder to pore-forming agent in the mixed powder is 50:50.
[0128] The layered mixed powder comprises sequentially laying a lower layer of mixed powder with a thickness of 100 μm, a middle layer of mixed powder with a thickness of 220 μm, and an upper layer of mixed powder with a thickness of 350 μm; in the lower layer of mixed powder, the average particle size of the pore-forming agent is 50 μm; in the middle layer of mixed powder, the average particle size of the pore-forming agent is 125 μm; and in the upper layer of mixed powder, the average particle size of the pore-forming agent is 250 μm.
[0129] (3) In an argon atmosphere, the green blank is subjected to pressure sintering; then, under pressure holding conditions, it is cooled to room temperature at a cooling rate of 10℃ / min, the pressure is removed, and the sintered product is obtained.
[0130] The heating rate of the pressure sintering is 2℃ / min, the sintering temperature is 900℃, the pressure is 20MPa, and the holding time is 6h.
[0131] (4) The sintered product is washed with water to remove the pore-forming agent, then acid-washed to remove the surface oxide layer, and dried to obtain NiTi foam;
[0132] The water washing method includes ultrasonic cleaning at a temperature of 50°C for 8 hours.
[0133] The pickling was carried out using a 3wt% hydrofluoric acid solution for 60 seconds.
[0134] (5) The NiTi foam is immersed in a chemical copper plating solution for 1 hour, and after washing and drying, the current collector for the negative electrodeless battery is obtained.
[0135] The electroless copper plating solution can be composed of equal volumes of solution A and solution B; solution A consists of 12 g / L NaOH, 13 g / L CuSO4·5H2O, and 29 g / L NaKC4H4O6·4H2O, with water as the solvent; solution B is a 9.5 mL / L methanol aqueous solution.
[0136] Example 3
[0137] This embodiment provides a method for preparing a current collector for a negative electrodeless battery, including:
[0138] (1) Ni powder and Ti powder are mixed in a molar ratio of 1:1, and then arc-melted in an argon atmosphere. The mixture is then cooled and cast to obtain NiTi alloy rods. The NiTi alloy rods are crushed to obtain NiTi alloy powder with an average particle size of 30 μm.
[0139] The electric arc melting temperature is 1700℃ and the time is 10 minutes;
[0140] The cooling rate of the cooling casting is 20℃ / min;
[0141] (2) The mixed powder is laid in layers and then pre-pressed with a pressure of 100MPa to obtain a green body;
[0142] The mixed powder comprises NiTi alloy powder, pore-forming agent (ammonium bicarbonate) and dispersant (anhydrous ethanol); the volume ratio of NiTi alloy powder to pore-forming agent in the mixed powder is 70:30.
[0143] The layered mixed powder comprises sequentially laying a lower layer of mixed powder with a thickness of 180 μm, a middle layer of mixed powder with a thickness of 350 μm, and an upper layer of mixed powder with a thickness of 550 μm; in the lower layer of mixed powder, the average particle size of the pore-forming agent is 125 μm; in the middle layer of mixed powder, the average particle size of the pore-forming agent is 250 μm; and in the upper layer of mixed powder, the average particle size of the pore-forming agent is 500 μm.
[0144] (3) In an argon atmosphere, the green blank is subjected to pressure sintering; then, under pressure holding conditions, it is cooled to room temperature at a cooling rate of 20℃ / min, the pressure is removed, and the sintered product is obtained.
[0145] The heating rate of the pressure sintering is 10℃ / min, the sintering temperature is 1000℃, the pressure is 30MPa, and the holding time is 3h.
[0146] (4) The sintered product is washed with water to remove the pore-forming agent, then acid-washed to remove the surface oxide layer, and dried to obtain NiTi foam;
[0147] The water washing method includes ultrasonic cleaning at a temperature of 80°C for 4 hours;
[0148] The pickling was carried out using an 8 wt% hydrofluoric acid solution for 20 seconds.
[0149] (5) The NiTi foam is immersed in a chemical copper plating solution for 3 hours for chemical copper plating, and then washed and dried to obtain the current collector for the negative electrodeless battery;
[0150] The electroless copper plating solution can be composed of equal volumes of solution A and solution B; solution A consists of 12 g / L NaOH, 13 g / L CuSO4·5H2O, and 29 g / L NaKC4H4O6·4H2O, with water as the solvent; solution B is a 9.5 mL / L methanol aqueous solution.
[0151] Example 4
[0152] This embodiment provides a method for preparing a current collector for a negative electrodeless battery, including:
[0153] (1) Ni powder and Ti powder are mixed in a molar ratio of 1:1, and then arc-melted in an argon atmosphere. The mixture is then cooled and cast to obtain NiTi alloy rods. The NiTi alloy rods are crushed to obtain NiTi alloy powder with an average particle size of 25 μm.
[0154] The electric arc melting temperature was 1620℃, and the time was 18 minutes.
[0155] The cooling rate of the cooling casting is 12℃ / min;
[0156] (2) The mixed powder is laid in layers and then pre-pressed with a pressure of 70MPa to obtain a green body;
[0157] The mixed powder comprises NiTi alloy powder, pore-forming agent (ammonium bicarbonate) and dispersant (anhydrous ethanol); the volume ratio of NiTi alloy powder to pore-forming agent in the mixed powder is 55:45.
[0158] The layered mixed powder comprises sequentially laying a lower layer of mixed powder with a thickness of 150 μm, a middle layer of mixed powder with a thickness of 300 μm, and an upper layer of mixed powder with a thickness of 450 μm; in the lower layer of mixed powder, the average particle size of the pore-forming agent is 80 μm; in the middle layer of mixed powder, the average particle size of the pore-forming agent is 200 μm; and in the upper layer of mixed powder, the average particle size of the pore-forming agent is 350 μm.
[0159] (3) In an argon atmosphere, the green blank is subjected to pressure sintering; then, under pressure holding conditions, it is cooled to room temperature at a cooling rate of 12℃ / min, the pressure is removed, and the sintered product is obtained.
[0160] The heating rate of the pressure sintering is 5℃ / min, the sintering temperature is 920℃, the pressure is 22MPa, and the holding time is 5h.
[0161] (4) The sintered product is washed with water to remove the pore-forming agent, then acid-washed to remove the surface oxide layer, and dried to obtain NiTi foam;
[0162] The water washing method includes ultrasonic cleaning at a temperature of 60°C for 7 hours.
[0163] The pickling was carried out using a 4 wt% hydrofluoric acid solution for 50 seconds.
[0164] (5) The NiTi foam is immersed in a chemical copper plating solution for 1.5 hours for chemical copper plating, and then washed and dried to obtain the current collector for the negative electrodeless battery;
[0165] The electroless copper plating solution can be composed of equal volumes of solution A and solution B; solution A consists of 12 g / L NaOH, 13 g / L CuSO4·5H2O, and 29 g / L NaKC4H4O6·4H2O, with water as the solvent; solution B is a 9.5 mL / L methanol aqueous solution.
[0166] Example 5
[0167] This embodiment provides a method for preparing a current collector for a negative electrodeless battery, including:
[0168] (1) Ni powder and Ti powder are mixed in a molar ratio of 1:1, and then arc-melted in an argon atmosphere. The mixture is then cooled and cast to obtain NiTi alloy rods. The NiTi alloy rods are crushed to obtain NiTi alloy powder with an average particle size of 25 μm.
[0169] The electric arc melting temperature was 1680℃, and the time was 12 minutes;
[0170] The cooling rate of the cooling casting is 18°C / min;
[0171] (2) The mixed powder is laid in layers and then pre-pressed with a pressure of 90MPa to obtain a green body;
[0172] The mixed powder comprises NiTi alloy powder, pore-forming agent (ammonium bicarbonate) and dispersant (anhydrous ethanol); the volume ratio of NiTi alloy powder to pore-forming agent in the mixed powder is 65:35.
[0173] The layered mixed powder comprises sequentially laying a lower layer of mixed powder with a thickness of 150 μm, a middle layer of mixed powder with a thickness of 300 μm, and an upper layer of mixed powder with a thickness of 450 μm; in the lower layer of mixed powder, the average particle size of the pore-forming agent is 80 μm; in the middle layer of mixed powder, the average particle size of the pore-forming agent is 200 μm; and in the upper layer of mixed powder, the average particle size of the pore-forming agent is 350 μm.
[0174] (3) In an argon atmosphere, the green blank is subjected to pressure sintering; then, under pressure holding conditions, it is cooled to room temperature at a cooling rate of 18°C / min, the pressure is removed, and the sintered product is obtained.
[0175] The pressure sintering process involves a heating rate of 8°C / min, a sintering temperature of 980°C, a pressure of 28 MPa, and a holding time of 3.5 h.
[0176] (4) The sintered product is washed with water to remove the pore-forming agent, then acid-washed to remove the surface oxide layer, and dried to obtain NiTi foam;
[0177] The water washing method includes ultrasonic cleaning at a temperature of 70°C for 5 hours.
[0178] The pickling was carried out using a 6 wt% hydrofluoric acid solution for 30 seconds.
[0179] (5) The NiTi foam is immersed in a chemical copper plating solution for 2.5 hours for chemical copper plating, and then washed and dried to obtain the current collector for the negative electrodeless battery;
[0180] The electroless copper plating solution can be composed of equal volumes of solution A and solution B; solution A consists of 12 g / L NaOH, 13 g / L CuSO4·5H2O, and 29 g / L NaKC4H4O6·4H2O, with water as the solvent; solution B is a 9.5 mL / L methanol aqueous solution.
[0181] Example 6
[0182] This embodiment provides a method for preparing a current collector for a negative electrodeless battery. Except for the layered mixing powder preparation, which involves sequentially laying a lower layer of mixing powder and a middle layer of mixing powder, the rest is the same as in Embodiment 1, including:
[0183] (1) Ni powder and Ti powder are mixed in a molar ratio of 1:1, and then arc-melted in an argon atmosphere. The mixture is then cooled and cast to obtain NiTi alloy rods. The NiTi alloy rods are crushed to obtain NiTi alloy powder with an average particle size of 25 μm.
[0184] The electric arc melting temperature is 1650℃ and the time is 15 minutes;
[0185] The cooling rate of the cooling casting is 15℃ / min;
[0186] (2) The mixed powder is laid in layers and then pre-pressed with a pressure of 80 MPa to obtain a green body with the same thickness as in Example 1;
[0187] The mixed powder comprises NiTi alloy powder, pore-forming agent (ammonium bicarbonate) and dispersant (anhydrous ethanol); the volume ratio of NiTi alloy powder to pore-forming agent in the mixed powder is 60:40.
[0188] The layered mixed powder includes sequentially laying a lower layer of mixed powder and a middle layer of mixed powder; in the lower layer of mixed powder, the average particle size of the pore-forming agent is 80 μm; in the middle layer of mixed powder, the average particle size of the pore-forming agent is 200 μm; wherein, the laying thickness ratio of the lower layer of mixed powder and the middle layer of mixed powder is the same as in Example 1;
[0189] (3) In an argon atmosphere, the green blank is subjected to pressure sintering; then, under pressure holding conditions, it is cooled to room temperature at a cooling rate of 15℃ / min, the pressure is removed, and the sintered product is obtained.
[0190] The heating rate of the pressure sintering is 6℃ / min, the sintering temperature is 950℃, the pressure is 25MPa, and the holding time is 4h.
[0191] (4) The sintered product is washed with water to remove the pore-forming agent, then acid-washed to remove the surface oxide layer, and dried to obtain NiTi foam;
[0192] The water washing method includes ultrasonic cleaning at a temperature of 65°C for 6 hours;
[0193] The pickling was carried out using a 5 wt% hydrofluoric acid solution for 40 seconds.
[0194] (5) The NiTi foam is immersed in a chemical copper plating solution for 2 hours for chemical copper plating, and then washed and dried to obtain the current collector for the negative electrodeless battery;
[0195] The electroless copper plating solution can be composed of equal volumes of solution A and solution B; solution A consists of 12 g / L NaOH, 13 g / L CuSO4·5H2O, and 29 g / L NaKC4H4O6·4H2O, with water as the solvent; solution B is a 9.5 mL / L methanol aqueous solution.
[0196] Example 7
[0197] This embodiment provides a method for preparing a current collector for a negative electrodeless battery. Except for the layered mixing powder preparation, which involves sequentially laying a middle layer of mixing powder and an upper layer of mixing powder, the rest is the same as in Embodiment 1, including:
[0198] (1) Ni powder and Ti powder are mixed in a molar ratio of 1:1, and then arc-melted in an argon atmosphere. The mixture is then cooled and cast to obtain NiTi alloy rods. The NiTi alloy rods are crushed to obtain NiTi alloy powder with an average particle size of 25 μm.
[0199] The electric arc melting temperature is 1650℃ and the time is 15 minutes;
[0200] The cooling rate of the cooling casting is 15℃ / min;
[0201] (2) The mixed powder is laid in layers and then pre-pressed with a pressure of 80 MPa to obtain a green body with the same thickness as in Example 1;
[0202] The mixed powder comprises NiTi alloy powder, pore-forming agent (ammonium bicarbonate) and dispersant (anhydrous ethanol); the volume ratio of NiTi alloy powder to pore-forming agent in the mixed powder is 60:40.
[0203] The layered mixed powder includes sequentially laying a middle layer of mixed powder and a top layer of mixed powder; in the middle layer of mixed powder, the average particle size of the pore-forming agent is 200 μm; in the top layer of mixed powder, the average particle size of the pore-forming agent is 350 μm; wherein, the laying thickness ratio of the middle layer of mixed powder and the top layer of mixed powder is the same as in Example 1;
[0204] (3) In an argon atmosphere, the green blank is subjected to pressure sintering; then, under pressure holding conditions, it is cooled to room temperature at a cooling rate of 15℃ / min, the pressure is removed, and the sintered product is obtained.
[0205] The heating rate of the pressure sintering is 6℃ / min, the sintering temperature is 950℃, the pressure is 25MPa, and the holding time is 4h.
[0206] (4) The sintered product is washed with water to remove the pore-forming agent, then acid-washed to remove the surface oxide layer, and dried to obtain NiTi foam;
[0207] The water washing method includes ultrasonic cleaning at a temperature of 65°C for 6 hours;
[0208] The pickling was carried out using a 5 wt% hydrofluoric acid solution for 40 seconds.
[0209] (5) The NiTi foam is immersed in a chemical copper plating solution for 2 hours for chemical copper plating, and then washed and dried to obtain the current collector for the negative electrodeless battery;
[0210] The electroless copper plating solution can be composed of equal volumes of solution A and solution B; solution A consists of 12 g / L NaOH, 13 g / L CuSO4·5H2O, and 29 g / L NaKC4H4O6·4H2O, with water as the solvent; solution B is a 9.5 mL / L methanol aqueous solution.
[0211] Example 8
[0212] This embodiment provides a method for preparing a current collector for a negative electrodeless battery, which, in addition to the layered spreading of the mixed powder comprising sequentially spreading a lower layer of mixed powder and an upper layer of mixed powder, includes:
[0213] (1) Ni powder and Ti powder are mixed in a molar ratio of 1:1, and then arc-melted in an argon atmosphere. The mixture is then cooled and cast to obtain NiTi alloy rods. The NiTi alloy rods are crushed to obtain NiTi alloy powder with an average particle size of 25 μm.
[0214] The electric arc melting temperature is 1650℃ and the time is 15 minutes;
[0215] The cooling rate of the cooling casting is 15℃ / min;
[0216] (2) The mixed powder is laid in layers and then pre-pressed with a pressure of 80 MPa to obtain a green body with the same thickness as in Example 1;
[0217] The mixed powder comprises NiTi alloy powder, pore-forming agent (ammonium bicarbonate) and dispersant (anhydrous ethanol); the volume ratio of NiTi alloy powder to pore-forming agent in the mixed powder is 60:40.
[0218] The layered mixed powder includes sequentially laying a lower layer of mixed powder and an upper layer of mixed powder; in the lower layer of mixed powder, the average particle size of the pore-forming agent is 80 μm; in the upper layer of mixed powder, the average particle size of the pore-forming agent is 350 μm; wherein, the laying thickness ratio of the lower layer of mixed powder and the upper layer of mixed powder is the same as in Example 1;
[0219] (3) In an argon atmosphere, the green blank is subjected to pressure sintering; then, under pressure holding conditions, it is cooled to room temperature at a cooling rate of 15℃ / min, the pressure is removed, and the sintered product is obtained.
[0220] The heating rate of the pressure sintering is 6℃ / min, the sintering temperature is 950℃, the pressure is 25MPa, and the holding time is 4h.
[0221] (4) The sintered product is washed with water to remove the pore-forming agent, then acid-washed to remove the surface oxide layer, and dried to obtain NiTi foam;
[0222] The water washing method includes ultrasonic cleaning at a temperature of 65°C for 6 hours;
[0223] The pickling was carried out using a 5 wt% hydrofluoric acid solution for 40 seconds.
[0224] (5) The NiTi foam is immersed in a chemical copper plating solution for 2 hours for chemical copper plating, and then washed and dried to obtain the current collector for the negative electrodeless battery;
[0225] The electroless copper plating solution can be composed of equal volumes of solution A and solution B; solution A consists of 12 g / L NaOH, 13 g / L CuSO4·5H2O, and 29 g / L NaKC4H4O6·4H2O, with water as the solvent; solution B is a 9.5 mL / L methanol aqueous solution.
[0226] Comparative Example 1
[0227] This comparative example provides a method for preparing a current collector for a negative electrodeless battery. Except for the absence of layered mixed powder layering, where only the lower layer of mixed powder is laid, the method is identical to that in Example 1, including:
[0228] (1) Ni powder and Ti powder are mixed in a molar ratio of 1:1, and then arc-melted in an argon atmosphere. The mixture is then cooled and cast to obtain NiTi alloy rods. The NiTi alloy rods are crushed to obtain NiTi alloy powder with an average particle size of 25 μm.
[0229] The electric arc melting temperature is 1650℃ and the time is 15 minutes;
[0230] The cooling rate of the cooling casting is 15℃ / min;
[0231] (2) The mixed powder is laid out and then pre-pressed with a pressure of 80 MPa to obtain a green body with the same thickness as in Example 1;
[0232] The mixed powder comprises NiTi alloy powder, pore-forming agent (ammonium bicarbonate) and dispersant (anhydrous ethanol); the volume ratio of NiTi alloy powder to pore-forming agent in the mixed powder is 60:40.
[0233] The laying of the mixed powder includes laying a lower layer of mixed powder; in the lower layer of mixed powder, the average particle size of the pore-forming agent is 80 μm;
[0234] (3) In an argon atmosphere, the green blank is subjected to pressure sintering; then, under pressure holding conditions, it is cooled to room temperature at a cooling rate of 15℃ / min, the pressure is removed, and the sintered product is obtained.
[0235] The heating rate of the pressure sintering is 6℃ / min, the sintering temperature is 950℃, the pressure is 25MPa, and the holding time is 4h.
[0236] (4) The sintered product is washed with water to remove the pore-forming agent, then acid-washed to remove the surface oxide layer, and dried to obtain NiTi foam;
[0237] The water washing method includes ultrasonic cleaning at a temperature of 65°C for 6 hours;
[0238] The pickling was carried out using a 5 wt% hydrofluoric acid solution for 40 seconds.
[0239] (5) The NiTi foam is immersed in a chemical copper plating solution for 2 hours for chemical copper plating, and then washed and dried to obtain the current collector for the negative electrodeless battery;
[0240] The electroless copper plating solution can be composed of equal volumes of solution A and solution B; solution A consists of 12 g / L NaOH, 13 g / L CuSO4·5H2O, and 29 g / L NaKC4H4O6·4H2O, with water as the solvent; solution B is a 9.5 mL / L methanol aqueous solution.
[0241] Comparative Example 2
[0242] This comparative example provides a method for preparing a current collector for a negative electrodeless battery. Except for the absence of layered mixed powder layering, where only a middle layer of mixed powder is laid, the method is identical to that in Example 1, including:
[0243] (1) Ni powder and Ti powder are mixed in a molar ratio of 1:1, and then arc-melted in an argon atmosphere. The mixture is then cooled and cast to obtain NiTi alloy rods. The NiTi alloy rods are crushed to obtain NiTi alloy powder with an average particle size of 25 μm.
[0244] The electric arc melting temperature is 1650℃ and the time is 15 minutes;
[0245] The cooling rate of the cooling casting is 15℃ / min;
[0246] (2) The mixed powder is laid out and then pre-pressed with a pressure of 80 MPa to obtain a green body with the same thickness as in Example 1;
[0247] The mixed powder comprises NiTi alloy powder, pore-forming agent (ammonium bicarbonate) and dispersant (anhydrous ethanol); the volume ratio of NiTi alloy powder to pore-forming agent in the mixed powder is 60:40.
[0248] The laying of the mixed powder includes laying a middle layer of mixed powder; in the middle layer of mixed powder, the average particle size of the pore-forming agent is 200 μm;
[0249] (3) In an argon atmosphere, the green blank is subjected to pressure sintering; then, under pressure holding conditions, it is cooled to room temperature at a cooling rate of 15℃ / min, the pressure is removed, and the sintered product is obtained.
[0250] The heating rate of the pressure sintering is 6℃ / min, the sintering temperature is 950℃, the pressure is 25MPa, and the holding time is 4h.
[0251] (4) The sintered product is washed with water to remove the pore-forming agent, then acid-washed to remove the surface oxide layer, and dried to obtain NiTi foam;
[0252] The water washing method includes ultrasonic cleaning at a temperature of 65°C for 6 hours;
[0253] The pickling was carried out using a 5 wt% hydrofluoric acid solution for 40 seconds.
[0254] (5) The NiTi foam is immersed in a chemical copper plating solution for 2 hours for chemical copper plating, and then washed and dried to obtain the current collector for the negative electrodeless battery;
[0255] The electroless copper plating solution can be composed of equal volumes of solution A and solution B; solution A consists of 12 g / L NaOH, 13 g / L CuSO4·5H2O, and 29 g / L NaKC4H4O6·4H2O, with water as the solvent; solution B is a 9.5 mL / L methanol aqueous solution.
[0256] Comparative Example 3
[0257] This comparative example provides a method for preparing a current collector for a negative electrodeless battery. Except for the absence of layered mixed powder layering, where only the upper layer of mixed powder is laid, the method is identical to that of Example 1, including:
[0258] (1) Ni powder and Ti powder are mixed in a molar ratio of 1:1, and then arc-melted in an argon atmosphere. The mixture is then cooled and cast to obtain NiTi alloy rods. The NiTi alloy rods are crushed to obtain NiTi alloy powder with an average particle size of 25 μm.
[0259] The electric arc melting temperature is 1650℃ and the time is 15 minutes;
[0260] The cooling rate of the cooling casting is 15℃ / min;
[0261] (2) The mixed powder is laid out and then pre-pressed with a pressure of 80 MPa to obtain a green body with the same thickness as in Example 1;
[0262] The mixed powder comprises NiTi alloy powder, pore-forming agent (ammonium bicarbonate) and dispersant (anhydrous ethanol); the volume ratio of NiTi alloy powder to pore-forming agent in the mixed powder is 60:40.
[0263] The laying of the mixed powder includes laying an upper layer of mixed powder; in the upper layer of mixed powder, the average particle size of the pore-forming agent is 350 μm;
[0264] (3) In an argon atmosphere, the green blank is subjected to pressure sintering; then, under pressure holding conditions, it is cooled to room temperature at a cooling rate of 15℃ / min, the pressure is removed, and the sintered product is obtained.
[0265] The heating rate of the pressure sintering is 6℃ / min, the sintering temperature is 950℃, the pressure is 25MPa, and the holding time is 4h.
[0266] (4) The sintered product is washed with water to remove the pore-forming agent, then acid-washed to remove the surface oxide layer, and dried to obtain NiTi foam;
[0267] The water washing method includes ultrasonic cleaning at a temperature of 65°C for 6 hours;
[0268] The pickling was carried out using a 5 wt% hydrofluoric acid solution for 40 seconds.
[0269] (5) The NiTi foam is immersed in a chemical copper plating solution for 2 hours for chemical copper plating, and then washed and dried to obtain the current collector for the negative electrodeless battery;
[0270] The electroless copper plating solution can be composed of equal volumes of solution A and solution B; solution A consists of 12 g / L NaOH, 13 g / L CuSO4·5H2O, and 29 g / L NaKC4H4O6·4H2O, with water as the solvent; solution B is a 9.5 mL / L methanol aqueous solution.
[0271] Performance Characterization
[0272] Using the current collector for a negative electrodeless battery provided in the above embodiments and comparative examples, a CR2032 coin cell was assembled in an inert atmosphere glove box: a sodium sheet was used as the counter electrode, the current collector for a negative electrodeless battery was used as the working electrode, an electrolyte (1 mol / L NaClO4 dissolved in ethylene carbonate (EC) / diethyl carbonate (DEC) (volume ratio 1:1), and 5 vol% fluoroethylene carbonate (FEC) additive was added) was added, and a CR2032 coin cell was assembled.
[0273] First coulombic efficiency test of the battery: After resting for 12 hours, charge to 3.6V with constant current and constant voltage at 0.1C, then rest for another 0.5 hours, and then discharge to 2.0V with constant current at 0.1C. Calculate the ratio of battery discharge capacity to charge capacity.
[0274] Cycle life test: After resting for 12 hours, charge to 3.6V at 0.5C constant current and constant voltage at room temperature, rest for 0.5 hours, and then discharge to 2.0V at 0.5C constant current. Cycle 100 times and record the capacity retention rate.
[0275] The test results are shown in Table 1.
[0276] Table 1
[0277]
[0278] As can be seen from Examples 1 to 5 in Table 1, the current collector provided by the present invention can significantly improve the first-cycle coulombic efficiency and long-cycle capacity retention of the sodium battery without a negative electrode.
[0279] A comparison of Examples 6, 7, and 8 with Example 1 shows that the absence of upper, lower, or middle mixed powder in the current collector will cause a decrease in battery performance. In Example 6, the absence of upper mixed powder means that the volume expansion stress during discharge cannot be effectively absorbed, the sodium deposition layer is prone to cracking, and dead sodium is generated, leading to a decrease in cycle performance. In Example 7, the absence of lower mixed powder means that sodium cannot be preferentially driven to deposit densely at the bottom, increasing the initial irreversible capacity and reducing the first-efficiency performance. In Example 8, the absence of middle mixed powder results in discontinuous stress transmission; the matrix cannot be uniformly pressurized during austenite contraction, leading to loose and porous sodium deposition, a large accumulation of dead sodium, and a decrease in both the first-efficiency performance and cycle performance.
[0280] Comparison of Comparative Examples 1, 2, and 3 with Example 1 shows that when only a single lower, middle, or upper layer of mixed powder is used, it is impossible to achieve both high initial efficiency and long cycle stability at the same time.
[0281] In summary, this invention prepares a NiTi foam matrix through a layered gradient pore-forming and pressure sintering process, followed by chemical copper plating to obtain a composite current collector. A longitudinal gradient pore structure is established along the thickness direction. Under low-temperature martensitic soft state, the current collector pores expand, reserving sufficient space to accommodate sodium deposition. During discharge, the Joule heating of the battery causes NiTi to transform into an austenitic contractile phase. The entire matrix applies uniform pressure to the sodium deposition layer, and the stress concentration in the lower small-pore region allows for preferential contraction, driving dense sodium deposition at the bottom of the current collector and inhibiting top-down dendrite growth. The upper large-pore region simultaneously buffers volume expansion stress. After discharge, the battery cools naturally, and the NiTi matrix returns to its expanded soft state, reforming large-size sodium storage pores. This invention relies solely on the battery's own heat generation and dissipation to achieve adaptive pore regulation, upgrading the traditional passive sodium storage mode of the current collector to active stress-regulated sodium storage. The matrix and gradient pore functions are integrated, avoiding coating failure issues, effectively reducing dead sodium generation, and improving the battery's long-cycle stability.
[0282] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A method for preparing a current collector for a negative electrodeless battery, characterized in that, The preparation method includes: S1. The mixed powder is laid in layers and then pre-pressed to obtain a green body; The mixed powder includes NiTi alloy powder, pore-forming agent and dispersant; along the thickness direction of the layer, the average particle size of the pore-forming agent increases gradually in different layers of the mixed powder. S2. In a protective atmosphere, the green compact is subjected to pressure sintering; then, under pressure holding conditions, it is cooled to room temperature, the pressure is removed, and the sintered product is obtained. S3. Wash the sintered product with water to remove the pore-forming agent, then acid wash to remove the surface oxide layer, and dry to obtain NiTi foam; S4. The NiTi foam is immersed in a chemical copper plating solution for chemical copper plating, and after washing and drying, the current collector for the negative electrodeless battery is obtained.
2. The preparation method according to claim 1, characterized in that, The average particle size of the NiTi alloy powder is 20μm~30μm; And / or, the method for preparing the NiTi alloy powder includes: mixing Ni powder and Ti powder, performing arc melting in a protective atmosphere, cooling and casting to obtain NiTi alloy rods; crushing the NiTi alloy rods to obtain NiTi alloy powder.
3. The preparation method according to claim 2, characterized in that, The temperature of the electric arc melting is 1600℃~1700℃; And / or, the arc melting time is 10 min to 20 min; And / or, the cooling rate of the cooling casting is 10℃ / min to 20℃ / min.
4. The preparation method according to claim 1, characterized in that, The layered laying of mixed powder includes laying a lower layer of mixed powder, a middle layer of mixed powder, and an upper layer of mixed powder in sequence; In the lower layer of mixed powder, the average particle size of the pore-forming agent is 50μm~125μm; In the intermediate layer mixed powder, the average particle size of the pore-forming agent is 125μm~250μm; In the upper mixed powder, the average particle size of the pore-forming agent is 250μm~500μm.
5. The preparation method according to claim 1 or 4, characterized in that, In the mixed powder, the volume ratio of NiTi alloy powder to pore-forming agent is (50~70):(50~30); And / or, the pre-compression molding pressure is 50MPa~100MPa.
6. The preparation method according to claim 1, characterized in that, The heating rate of the pressure sintering is 2℃ / min to 10℃ / min; And / or, the sintering temperature of the pressure sintering is 900℃~1000℃; And / or, the pressure of the pressure sintering is 20MPa~30MPa; And / or, the holding time for the pressure sintering is 3h to 6h; And / or, the cooling rate is 10℃ / min to 20℃ / min.
7. The preparation method according to claim 1, characterized in that, The water washing method includes ultrasonic cleaning; And / or, the temperature of the water wash is 50℃~80℃; And / or, the washing time is 4h to 8h.
8. The preparation method according to claim 1 or 7, characterized in that, The pickling is carried out using a hydrofluoric acid solution with a concentration of 3wt% to 8wt%. And / or, the pickling time is 20s~60s.
9. A current collector for a negative electrodeless battery, characterized in that, The current collector for the negative electrodeless battery is prepared by the preparation method described in any one of claims 1 to 8.
10. A sodium-ion battery, characterized in that, The sodium-ion battery includes a current collector for a negative electrode-free battery prepared by the preparation method according to any one of claims 1 to 8, or includes the current collector for a negative electrode-free battery as described in claim 9.
Citation Information
Patent Citations
Three-dimensional porous current collector and preparation method and application thereof
CN119447319A
Three-dimensional network enhanced composite current collector, preparation method thereof and cathode-free battery
CN121862753A